In Situ Cutting Methodology with 3D Measurement of Block Excesses in Shipbuilding - Aydin, Berk; Turan, Eda (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2024)
The ship construction process is characterized by a sequential workflow, with pivotal workstations double dagger playing a crucial role. Initially, steel plates are introduced to these stations in sheet form, undergoing a transformation process that culminates in the creation of segments known as blocks double dagger. These blocks are individually constructed and subsequently assembled at the final workstation, denoted as the block joining station. Upon completing block fabrication, a deliberate tolerance allowance is retained on the plates to accommodate deformations induced by heat treatment during the transformation from plates to blocks. The alignment process involves aligning the reference points (master reference line) of the blocks on a common axis, facilitating the identification of excess material and deformations. This alignment process encompasses aligning the blocks with each other, employing either a three-dimensional measurement device or manual methods to obtain necessary measurements for determining excess material. In an effort to optimize time spent on block alignment and machine usage, a comprehensive methodology has been developed. This methodology involves determining excess material cuts on the blocks, performing virtual alignment operations using laser scanning techniques in a virtual environment, and conducting the cutting process on the slipway prior to placing the block excesses on it.
Keywords: block excesses; scanning techniques; three-dimensional scanning technology; REGISTRATION; Engineering